Methods to set transport service fees with the Apulian example of Brindisi port - Rossella Murgolo (European Regional Science Association (ERSA), 2005)
Setting fees in transport service has always been particularly important in economy both under a theoretical point of view and for the aims economic policies have to achieve by means of this instrument. In this view, the issue of the European Commission Green Book in 1997 - on ports and sea infrastructures - and that of the White Book in 1998 - referring to a fair set of fees to exploit infrastructures with an approach in stages in an UE context - led again to the debate on criteria to set transport infrastructures fees, particularly for ports. This paper aims to find a motion to review taxation on shipped and unloaded goods (art. 13, paragraph 1, letter c), act of 28th January 1994, no. 84) effective in the Brindisi port, Apulia, determined with ordinance no. 1/1999. Tax revision will occur referring to last years ISTAT indexes and considering the possibility of a higher levy to Harbour Authority necessary to improve services for passengers and goods movement. Variables of port fees will be set both for passengers and goods handling. Moreover, estimating transport demand elasticity in relation to price (fee) is essential to set fees variation. To set fees other ports taxes – comparable and/or competitor with the Brindisi port - will be taken into account together with the increase in management operational costs expected in 2004.
Keywords: 330